2017
DOI: 10.1080/15476286.2017.1409930
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerases IV and V influence the 3′ boundaries of Polymerase II transcription units in Arabidopsis

Abstract: Nuclear multisubunit RNA polymerases IV and V (Pol IV and Pol V) evolved in plants as specialized forms of Pol II. Their functions are best understood in the context of RNA-directed DNA methylation (RdDM), a process in which Pol IV-dependent 24 nt siRNAs direct the de novo cytosine methylation of regions transcribed by Pol V. Pol V has additional functions, independent of Pol IV and 24 nt siRNA biogenesis, in maintaining the repression of transposons and genomic repeats whose silencing depends on maintenance c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…This commonality of spurious sRNA transcripts in RdDM mutants is observed in nrpe1 very recently (Zheng et al, 2021) where a similar notion of chromatin relaxation triggering pol IV and pol II transcription is promulgated. Similarly, studies in maize and Arabidopsis have suggested atypical transcripts in the nrpd1 mutation (Erhard et al, 2015;McKinlay et al, 2018). Our studies mechanistically delineates the causative chromatin features in the nrpd1 mutant.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This commonality of spurious sRNA transcripts in RdDM mutants is observed in nrpe1 very recently (Zheng et al, 2021) where a similar notion of chromatin relaxation triggering pol IV and pol II transcription is promulgated. Similarly, studies in maize and Arabidopsis have suggested atypical transcripts in the nrpd1 mutation (Erhard et al, 2015;McKinlay et al, 2018). Our studies mechanistically delineates the causative chromatin features in the nrpd1 mutant.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, pol iv exhibits permanent loss of silencing at selected loci that are recalcitrant to rescue by complementation of pol IV and this phenomenon is due to associated loss of H3K9me2 marks . Unrestricted to silencing, it is also evidenced that loss of pol IV leads to transcriptional misregulation as observed by the accumulation of atypical nascent transcripts in maize (Erhard et al, 2015) and by increased pol II activity at 3'-ends of pol II transcriptional units (McKinlay et al, 2018). The indirect facilitation of spurious transcription by virtue of loss of epigenetic players triggers cryptic transcription units by pol II both in genes and transposons (Le et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Pol IV and Pol V activity also was linked to Pol II termination. Nuclear run‐on assays (Box 1) revealed that in approximately 12% of the protein‐coding genes, Pol II occupancy downstream of poly(A) sites significantly increases in pol IV or pol V mutants (McKinlay et al ., 2018). Further research combining GRO‐Seq (Box 1) with RNA‐Seq in mutant backgrounds related to epigenetics or RNA degradation will likely help to determine to what extent transcription is fine‐tuned by Polymerase collision of coding vs noncoding convergent transcriptional units.…”
Section: Long Noncoding Rnas Involved In Alternative Molecular Mechanmentioning
confidence: 99%
“…Although Pol IV and Pol V transcription is generally linked to the production of 24 nucleotide small interfering RNAs (24nt siRNAs) and the RNA-directed DNA methylation (RdDM) pathway [for review, see 13], Pol V transcripts have been also related to a broader spectrum of molecular mechanisms in the last few years. For instance, Pol V lncRNAs were shown to recruit components of the silencing machinery to promoter regions of protein-coding genes [14], to delimit Pol II transcriptional read-though [15], or to determine heterochromatin boundaries [16]. Plant Pol II lncRNAs have been involved in a varied assortment of molecular regulatory mechanisms impacting on gene expression, including chromatin remodeling and three-dimensional (3D) conformation dynamics, protein trafficking, modulation of alternative splicing, fine-tuning of miRNA activity, and control of mRNA translation or accumulation [3].…”
Section: Introductionmentioning
confidence: 99%